Masculinités variables en temps de crise : deux auteurs-compositeurs-interprètes : fixer le temps, de Dumas. Tacca / La Tribu, 2006 ; Les vendredis, de Stefie Shock. Atlantis, 2006 - Boisclair, Isabelle (Spirale, 2007)
https://id.erudit.org/iderudit/10364ac
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; arts; culture populaire; discipline; genre; hétérosexisme; masculinité; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; études littéraires

Lesbian inscriptions in francophone society and culture - Günther, Renate; Michallat, Wendy (Durham Modern Languages, 2007)
This book represents the first comprehensive collection of essays in English dedicated entirely to the study of lesbian inscriptions in francophone society and culture. Spanning the period from the early nineteenth to the twenty-first century, the volume offers a range of interdisciplinary perspectives on ways in which lesbianism has been represented and represented itself, with essays on poetry and the novel, contemporary film and television, photography and architecture. These essays will appeal to students and scholars of gender studies and French literature and culture.
Keywords: afrique; amériques; approches et analyses; arts; belgique; canada; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; régions géographiques; systèmes d'oppressions; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires